High paracellular nutrient absorption in intact bats is associated with high paracellular permeability in perfused intestinal segments - Brun, Antonio; Price, Edwin R.; Gontero-Fourcade, Manuel N.; Fernandez-Marinone, Guido; Cruz-Neto, Ariovaldo P. [UNESP]; Karasov, William H.; Caviedes-Vidal, Enrique (Company Of Biologists Ltd, 2014)
Water-soluble nutrients are absorbed by the small intestine via transcellular and paracellular mechanisms. Based on a few previous studies, the capacity for paracellular nutrient absorption seems greater in flying mammals than in nonflying mammals, but there has been little investigation of the mechanisms driving this difference. Therefore, we studied three species each of bats (Artibeus lituratus, Sturnira lilium and Carollia perspicillata) and nonflying mammals (Akodon montensis, Mus musculus and Rattus norvegicus). Using standard pharmacokinetic techniques in intact animals, we confirmed the greater paracellular nutrient absorption in the fliers, comparing one species in each group. Then we conducted in situ intestinal perfusions on individuals of all species. In both approaches, we measured the absorption of 3OMD-glucose, a nonmetabolizable glucose analog absorbed both paracellularly and transcellularly, as well as L-arabinose, which has no mediated transport. Fractional absorption of L-arabinose was three times higher in the bat (S. lilium: 1.2 +/- 0.24) than in the rodent (A. montensis: 0.35 +/- 0.04), whereas fractional absorption of 3OMD-glucose was complete in both species (1.46 +/- 0.4 and 0.97 +/- 0.12, respectively). In agreement, bats exhibited two to 12 times higher L-arabinose clearance per square centimeter nominal surface area than rodents in intestinal perfusions. Using L-arabinose, we estimated that the contribution of the paracellular pathway to total glucose absorption was higher in all three bats (109-137%) than in the rodents (13-39%). These findings contribute to an emerging picture that reliance on the paracellular pathway for nutrient absorption is much greater in bats relative to nonflying mammals and that this difference is driven by differences in intestinal permeability to nutrient-sized molecules.
Keywords: Intestine; Mediated absorption; Paracellular absorption; Arabinose; Flight; Bats; Intestinal perfusion; Akodon montensis; Sturnira lilium; Artibeus lituratus; Carollia perspicillata; Mus musculus; Rattus norvegicus